1997
DOI: 10.1002/(sici)1096-8628(19970516)70:2<107::aid-ajmg1>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Familial aplasia/hypoplasia of pelvis, femur, fibula, and ulna with abnormal digits in an inbred Pakistani Muslim family: A possible new autosomal recessive disorder with overlapping manifestations of the syndromes of Fuhrmann, Al-Awadi, and Raas-Rothschild

Abstract: We describe four affected children belonging to a large, highly inbred Muslim family originating from the North West Frontier Province of Pakistan. All children have a similar pattern of skeletal abnormalities, including aplasia/hypoplasia of the ulnae, hypoplasia of the pelvis, aplasia/hypoplasia of the femora, fibular aplasia, and variable digital abnormalities and absent/dysplastic nails. The phenotype overlaps with the syndromes of Fuhrmann, Al-Awadi, and Raas-Rothschild. The present and previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…AARRS is an autosomal recessive disorder, which is characterized by the presence of profound limb and pelvic deficiency, thoracic dystrophy, and genital anomalies. Limb anomalies consist of short and bowed radii, aplasia of ulna and fibula, hypoplastic or aplastic femur, hypoplasia/aplasia of tarsals, carpals, metatarsals, metacarpals, and phalanges [Al-Awadi et al, 1985;Richieri-Costa, 1987;Raas-Rothschild et al, 1988;Camera et al, 1993;Kumar et al, 1997]. The findings found in our patient appear similar to those of AARRS.…”
Section: Discussionsupporting
confidence: 79%
“…AARRS is an autosomal recessive disorder, which is characterized by the presence of profound limb and pelvic deficiency, thoracic dystrophy, and genital anomalies. Limb anomalies consist of short and bowed radii, aplasia of ulna and fibula, hypoplastic or aplastic femur, hypoplasia/aplasia of tarsals, carpals, metatarsals, metacarpals, and phalanges [Al-Awadi et al, 1985;Richieri-Costa, 1987;Raas-Rothschild et al, 1988;Camera et al, 1993;Kumar et al, 1997]. The findings found in our patient appear similar to those of AARRS.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, no defect of the ulna and a straight femur characterizes FATCO syndrome, whereas skeletal abnormalities in Fuhrmann syndrome include aplasia/hypoplasia of the ulna, hypoplasia of the pelvis, aplasia/hypoplasia of the femur, fibular aplasia, and variable digital abnormalities, as well as absent/dysplastic nails. In the family with Fuhrmann syndrome originally described by Kumar et al (12), Woods et al found an A109T mutation in the WNT7A gene, which controls the dorsoventral patterning (9). Overlap has been recognized between Fuhrmann syndrome and Al-Awadi/Raas-Rothschild syndrome (MIM 276820).…”
Section: Discussionmentioning
confidence: 99%
“…Overlap has been recognized between Fuhrmann syndrome and Al-Awadi/Raas-Rothschild syndrome (MIM 276820). Accordingly, Woods et al demonstrated a homozygous missense mutation in the WNT7A gene, R292C, in a consanguineous family in which three members had been diagnosed with Al-Awadi/Rass-Rothschild syndrome (12). In our case, absence of mutations in the WNT7A gene implies that FATCO syndrome and Furmann syndrome are distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Aplasia/hypoplasia of pelvis, femur, fibula, and ulna syndrome, described in four children from an inbred family by Kumar et al [1997]…”
Section: Discussionmentioning
confidence: 99%